2018
DOI: 10.1308/rcsann.2017.0230
|View full text |Cite
|
Sign up to set email alerts
|

Is sarcopenia a useful predictor of outcome in patients after emergency laparotomy? A study using the NELA database

Abstract: Introduction Studies have reported on the use of frailty as a prognostic indicator in patients undergoing elective surgery. Similar data do not exist for patients undergoing emergency surgery. The aim of this study was to evaluate the effect of preoperative sarcopenia measured by computed tomography (CT) on outcome following emergency laparotomy. Materials and methods Data from the National Emergency Laparotomy Audit database were retrieved for patients who had undergone an emergency laparotomy over 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…12,15,16 The values of the lower quartile for psoas attenuation in this study were 26 and 35.5 for unenhanced scans and enhanced scans, respectively, which is consistent with previous reported values ranging from 26 to 34 HU. 12,15,16 Previous studies did not address the effect of contrast enhancement on the association between psoas attenuation and postoperative outcomes, despite reports of a 10 HU difference between enhanced and unenhanced scans. 32,33 We therefore stratified for the presence of contrast enhancement in this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…12,15,16 The values of the lower quartile for psoas attenuation in this study were 26 and 35.5 for unenhanced scans and enhanced scans, respectively, which is consistent with previous reported values ranging from 26 to 34 HU. 12,15,16 Previous studies did not address the effect of contrast enhancement on the association between psoas attenuation and postoperative outcomes, despite reports of a 10 HU difference between enhanced and unenhanced scans. 32,33 We therefore stratified for the presence of contrast enhancement in this study.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that when stratified for contrast enhancement, psoas attenuation is an independent risk factor for both 30-day mortality and prolonged LOS, whereas the psoas PCSDs was not associated with either outcome. The greater importance of attenuation over the PCSDs has been reported in the emergency surgery setting 12 and in the elective surgery setting. 34 Our findings along with these studies suggest that muscle quality may be more important than muscle size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenic patients had increased 30-day (29.7% vs 8.7%; odds ratio 4.42; 95% CI 2.13–9.26; p < 0.001) and 1-year mortality (57.8% vs 18.5%; p < 0.001; odds ratio 6.05; 95% CI 3.28–11.18) when compared non-sarcopenic patients. 9 …”
Section: O Utcomementioning
confidence: 99%